Systematic review of guidelines for the diagnosis and treatment of Clostridioides difficile infection - Gu, Ting; Li, Wen; Yang, Li-Li; Yang, Si-Min; He, Qian; He, Hai-Yu; Sun, Da-Li (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To systematically assess the current related methodological quality of guidelines for the diagnosis and treatment of Clostridioides difficile infection (CDI), revealing the heterogeneity and reasons for guideline recommendations for the diagnosis and treatment of CDI. Methods: We searched electronic databases systematically between 2017 and 2021 to find the latest guidelines for the diagnosis and treatment of CDI. The Appraisal of Guidelines for Research and Evaluation (AGREE II) tool was used for quality assessment of the included guidelines. The main recommendations for the diagnosis and treatment of CDI in the guidelines were extracted and evaluated for consistency, and the level of evidence supporting these recommendations was further extracted and analysed. Results: Fourteen guidelines for the diagnosis and treatment of CDI were finally included in this study. There were four guidelines, BSG and HIS, ASCRS, IDSA AND SHEA, and NICE, with an overall score of more than 60%, which is worthy of clinical recommendation. Further analysis of the consistency of the main recommendations for the diagnosis and treatment of CDI in the guidelines showed that the recommendations differed among guidelines. There are no unified classification criteria for the severity of CDI in current studies; some recommendations for the diagnosis and treatment of CDI do not provide evidence to support the recommendations, most recommendations cite low levels of evidence, and there is a lack of high-quality research evidence. Conclusion: The quality of guidelines for the diagnosis and treatment of CDI is uneven. Recommendations on the diagnosis and treatment of CDI have also varied in the guidelines for the past 5 years. Improvements of the aforementioned factors associated with causing heterogeneity would be a rational approach by guideline developers to further update guidelines for the diagnosis and treatment of CDI.